The Historical Development of Labor Social Services in Algeria - benkhaled, djamel (Journal of Social Sciences and Humanities, 2016)
The importance of labor social services and their relationship with organizational culture is demonstrated through the effectiveness of management within Algerian economic enterprises on one hand, and through worker loyalty and commitment toward their organizations on the other. This stems from the fact that the worker plays a pivotal role in the development process, being both its primary means and its ultimate goal. Accordingly, this research attempts to identify the extent to which Algerian enterprises have kept pace with global economic and social changes since independence to the present day—specifically during the transition toward a market economy. This transition necessitates a shift in managerial culture, meaning a change in the set of principles and assumptions adopted by managers in their practices, as well as the behavioral standards related to the perception of human nature, the authoritarian dimension, the future vision of the enterprise, and the perspective on human relations. Today, organizational culture represents one of the most significant variables in the management strategy of both private and public organizations. In this study, we address the service aspect and its relationship with organizational culture within the Algerian economic enterprise, covering social, psychological, and formative dimensions, as well as organizational commitment. We argue that the existing problem in Algerian enterprises centers around mismanagement, poor leadership, and the inefficient organization and administration of labor social services.